Simplifying
16y^{2} + -12y + 2 = 0
Reorder the terms:
2 + -12y + 16y^{2} = 0
Solving
2 + -12y + 16y^{2} = 0
Solving for variable 'y'.
Factor out the Greatest Common Factor (GCF), '2'.
2(1 + -6y + 8y^{2}) = 0
Factor a trinomial.
2((1 + -4y)(1 + -2y)) = 0
Ignore the factor 2.
#### Subproblem 1

Set the factor '(1 + -4y)' equal to zero and attempt to solve:
Simplifying
1 + -4y = 0
Solving
1 + -4y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -4y = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -4y = 0 + -1
-4y = 0 + -1
Combine like terms: 0 + -1 = -1
-4y = -1
Divide each side by '-4'.
y = 0.25
Simplifying
y = 0.25
#### Subproblem 2

Set the factor '(1 + -2y)' equal to zero and attempt to solve:
Simplifying
1 + -2y = 0
Solving
1 + -2y = 0
Move all terms containing y to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -2y = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -2y = 0 + -1
-2y = 0 + -1
Combine like terms: 0 + -1 = -1
-2y = -1
Divide each side by '-2'.
y = 0.5
Simplifying
y = 0.5#### Solution

y = {0.25, 0.5}